1981
DOI: 10.1002/j.1552-4604.1981.tb01746.x
|View full text |Cite
|
Sign up to set email alerts
|

Chenodeoxycholic Acid and Ursodeoxycholic Acid Effects in Endogenous Hypertriglyceridemias. A Controlled Double‐Blind Trial

Abstract: A double-blind controlled trial was carried out to compare the effects of chenodeoxycholic acid (CDCA), ursodeoxycholic acid (UDCA), and placebo on cholesterol and triglyceride levels in patients with endogenous hypertriglyceridemias. The dose of both bile acids was four 150-mg capsules day. Total serum cholesterol levels did not show appreciable changes with any of the treatments. HDL cholesterol was significantly increased after CDCA but not after UDCA or placebo. CDCA feeding was associated with a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…We here investigated the effects of bile acids on TG homeostasis and confirmed that bile acids have a beneficial effect in hypertriglyceridemia (12,15,16,37). For these studies, we used KK-A y mice, a model for obesity and type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…We here investigated the effects of bile acids on TG homeostasis and confirmed that bile acids have a beneficial effect in hypertriglyceridemia (12,15,16,37). For these studies, we used KK-A y mice, a model for obesity and type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 69%
“…In humans, bile acid-binding resins induce the production of VLDL TGs (12)(13)(14), whereas treatment of cholesterol gallstones with the bile acid chenodeoxycholic acid (CDCA) has been shown to reduce hypertriglyceridemia (12,15,16). The mechanism underlying this reciprocal relationship between bile acid biosynthesis and TG production has remained elusive, but two possible explanations have been postulated.…”
Section: Introductionmentioning
confidence: 99%
“…Although the cause-and-effect relationship of this association has not been clarified, the results of the current study open the possibility that decreased activity of PPAR␣ could be the cause of both hypertriglyceridemia and decreased ileal bile salt absorption. The flux of bile salts through the enterohepatic circulation appears to have a direct effect on hepatic VLDL synthesis because patients administered CDCA exhibit decreased serum triglyceride concentrations (46). Conversely, interruption of the enterohepatic circulation of bile salts with cholestyramine transiently increases serum VLDL-triglyceride levels (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in dyslipidemic patients, bile acidbinding resins induce the hepatic production of VLDL triglycerides (TGs) [65 -67]. Furthermore, treatment with CDCA, which has been used in the past in patients with cholesterol gallstones, has been shown to reduce plasma TG levels [65,68,69]. The relationship between bile-acid signaling and TG homeostasis has been further highlighted by the observation that Fxr -/-mice have increased hepatic and serum triglyceride levels [8].…”
Section: Bile Acids Regulate Lipid Metabolismmentioning
confidence: 99%